Disability, education and employment in developing countries from charity to investment - Lamichhane, Kamal (Cambridge Univ. Press, 2015)
"Revolves around the discussion that human capital such as education and employment are the most important factors for inclusion and economic empowerment of the disabled, and their accessibility not only improves their livelihood, but also brightens the prospects of their poor families, and of the society as a whole"...Provided by publisher